The Role of Local Government in Conserving Pandan Wangi Rice Farming Land in Cianjur Regency - Einstein Anderson; Muh. Ilham; Faria Ruhana (Pusat Publikasi Nusantara, 2025)
Excessive conversion of agricultural land for industrial or residential uses has reduced the supply of pandan wangi rice due to shrinking farmland. This study aims to identify and analyze the local government’s role, the inhibiting factors, and efforts to overcome obstacles in preserving Pandan Wangi rice farming land in Cianjur Regency. Using a qualitative descriptive method based on Sondang P. Siagian’s theory (2009: 132), the research involved 18 informants and used primary and secondary data. Data collection included interviews, observation, and documentation, with analysis through data reduction, presentation, and conclusion drawing. Findings show the government protects Pandan Wangi rice land by formulating and enforcing regulations, notably Regional Regulation No. 19/2012 for Pandanwangi preservation, supported by Spatial Planning Regulation No. 4/2019. Integrated spatial planning uses agro-ecological maps and GIS for land zoning, buffer zones, and core area protection. Preservation is embedded in RPJMD/RKPD documents to align all sectoral policies with the protection of Pandanwangi fields. Routine coordination forums involve the Agriculture Service, Spatial Planning Service, Bappeda, Environmental Service, MP3C, and village governments. Stakeholder engagement includes farmer groups, MP3C, academics, NGOs, and market players in Village Musrenbang/Musrenbangcam, public forums, and technical workshops. Sustainable land management is enforced through soil and water conservation practices like terracing, legume rotation, organic mulch, and micro irrigation. Promotion and product image strengthening are achieved by supporting Geographical Indications for Pandanwangi rice to protect its authenticity and increase its premium market value.